Study on the Performance of Cold Spray Stainless Steel Coatings on Aluminum Alloy Surfaces - LIU Chenyang, JIANG Beiping, HUANG Guosheng, MA Li, JIANG Dan, MA Bojiang (Cailiao Baohu)
To study the effects of cold spraying process parameters on the performance of 430 stainless steel coatings on the surface of 3003 aluminum alloy，430 stainless steel magnetic conductive coatings were prepared on the surface of 3003 aluminum cookware using three different cold spraying process parameters.The microstructure，bonding strength and resistance to thermal shock of the coatings were analyzed using scanning electron microscopy (SEM)，tensile testing and thermal shock testing.Results showed that when spraying 430 stainless steel coating on the surface of 3003 aluminum alloy，the degree of oxidation and bonding strength of coatings increased with higher spraying temperatures and pressures.The oxygen content of the coatings reached a maximum of 0.55%(mass fraction)，and the bonding strength achieved a maximum of 31.78 MPa.The porosity decreased as the spraying temperature and pressure increased，reaching a minimum of 1.2%.The electrical conductivity ranged from 1.07 to 1.27 MS/m.During thermal shock testing over 100 cycles，the bonding strength decreased from 31.78 MPa to 28.67 MPa，with only a small reduction，and the electrical conductivity decreased to 1.05 MS/m.These results demonstrated that increasing cold spraying temperature and pressure significantly improved the microstructure and bonding properties of the coatings，thereby enhancing their reliability during use.Additionally，the cold-sprayed coatings exhibited excellent characteristics，including high bonding strength，low porosity and low oxidation levels，making this process highly advantageous for the production of magnetic conductive coatings on cookware.